Pengenalan sistem Refugia pada Lahan Pertanian di Desa Jalaksana, Kabupaten Kuningan - Amelia Paramitha Mahanani; Riski Ramazayandi; Jajang Suryana (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Pertanian Bogor, 2020)
One way to control pests of rice plants by using ornamental plants is known as Refugia. Planting refugia is one of the efforts to conserve natural enemies. Refugia is an area overgrown with several types of plants that can provide shelter, food sources or other resources for natural enemies such as predators and parasitoids. The Refugia technique is more economical and also certainly more environmentally friendly and health, because by using this technique we don't use chemicals that actually harm health. Agricultural systems that develop environmental-based pest control techniques, refugia are expected to maintain the sustainability of agroecosystems in the field, by following the principles of Integrated Pest Management. The purpose of this activity is to introduce the refugia system to farmers and provide a pilot as a refugia system application. The planting activity as an introduction to the refugia system is carried out in the area around agricultural land in the village of Jalaksana. The activity consisted of the socialization of the introduction of the refugia system and planting of species of refugia plants as a pilot. Key words: integrated pest control, pilot, refugia